Corporate restructuring : lessons from experience - Pomerleano, Michael; Shaw, William; World Bank. (Washington, D.C. : World Bank, 2005)
In the wake of the periodic financial crises of the late 1990s, the international financial institutions and many experts have recognized the need for a strategy to avoid and mitigate the severity of crises in the corporate sector. Addressing this problem requires the complementary efforts of policymakers, regulators, lawyers, insolvency experts, corporate restructuring specialists, and financiers. What are the roots of corporate distress? Can systemic corporate crises be predicted? What is the role of legal frameworks in preventing and coping with a crisis? What are the most effective financial techniques for dealing with distressed corporates? This timely volume takes a multidisciplinary perspective on corporate restructuring, and examines international experiences in dealing with corporate crises.
Presentations from a conference, "Corporate Restructuring--International Best Practices," hosted in March 2004 by the World Bank Group and held in Washington, D.C.
Includes bibliographical references.
lje 24/08/16
Loans
Keywords: Corporate reorganizations; Consolidation and merger of corporations; Financial crises; Bankruptcy; International finance